A Case for the Adoption of Virtual Annual General Meetings by Public Companies in Nigeria Post the COVID-19 Pandemic - Ukwu, Iguwo; Okechukwu Ukwueze, Festus (Law, State and Telecommunications Review, 2024)
[Purpose] The aim of the article is to make a case for Nigerian public companies to hold their annual general meetings (AGMs) on virtual platforms following the experiences during the Coronavirus Disease (COVID-19) pandemic and the physical and social distancing measures it occasioned. [Methodology/Approach/Design] The article followed a structured review of the extant companies’ regulation in Nigeria, particularly the Companies and Allied Matters Act, 2020 (CAMA 2020) drawing from the position of the law in other countries, both developing and developed countries. [Findings] It finds that prior to and during the COVID-19 pandemic, Nigerian company regulations made clear provisions for private companies to hold general meetings online but the provisions of the regulations were inadequate to support Nigerian public companies holding their AGMs on virtual platforms. [Practical Implications] The implication was that until recently, Nigeria public companies could only hold their AGMs physically. The Business Facilitation (Miscellaneous Provisions) Act, 2022 however amended (CAMA 2020) to provide for public companies to hold their general meeting on virtual platforms when necessary such as was the case during the COVID-19 pandemic. [Originality/Value] Given the importance and primacy of the general meeting in corporate governance, the availability of suitable information communication technology and the need for public companies to hold their AGMs even under pandemic situation, there is a need for public companies to take advantage of the recent change in the law and hold their general meetings on virtual platforms whenever the need arises.